Characteristics of 5-aminolaevulinic acid-induced protoporphyrin IX fluorescence in human skin in vivo - Ibbotson, S. H.; Jong, C.; Lesar, A.; Ferguson, J. S.; Padgett, M.; O'Dwyer, M.; Barnetson, R.; Ferguson, J. (Photodermatology, photoimmunology & photomedicine, 2006)
Background/Purpose: Topical photodynamic therapy (PDT) is increasingly being used to treat skin cancers. Knowledge of the detailed characteristics of 5‐aminolaevulinic acid (ALA)‐induced protoporphyrin IX (PpIX) fluorescence in diseased and normal skin is incomplete. Understanding the characteristics of PpIX fluorescence in normal skin may facilitate optimization of PDT regimes while minimizing side effects in the surrounding normal skin. We investigated the characteristics of ALA‐induced PpIX fluorescence in normal skin. Methods: ALA was applied to the arm, back and leg skin of 21 healthy volunteers for 1–6 h, and PpIX fluorescence was measured for up to 24 h after ALA application using a fluorescent spectrometer. The effect of tape stripping on fluorescence was also examined. Results: Considerable inter‐subject variation was observed in the time to reach peak PpIX fluorescence. Intra‐subject variation in the time to peak fluorescence was dependent on ALA application time. Six hours after ALA application, no significant difference was observed in the degree of fluorescence achieved irrespective of ALA application times ranging between 1 and 6 h. PpIX fluorescence was reduced on the leg and increased by tape stripping. Conclusions: Marked inter‐ and intra‐subject variation in ALA‐induced PpIX fluorescence occurs in normal human skin. ALA application time, body site and the state of the stratum corneum are all determinants of PpIX fluorescence within subjects and these factors need to be taken into account in optimization of PDT regimes.